Emotion Regulation as a Moderator of the Relationship between Family Functioning and Anxiety Generation Z - Angelina, Stephanie; Sahrani, Riana; Heng, Pamela Hendra (Psyche 165 Journal, 2025)
This study examines the role of family functioning on anxiety moderated by emotion regulation. Anxiety is a negative emotion characterized by worry and uncertainty about the future. One cause of anxiety is family functioning that isn't going well. Family functioning is the ability of the family to meet the needs of its members by overcoming problems, pressures, and supporting each other. To minimize the occurrence of high anxiety caused by family functioning that is not optimal, individuals need emotion regulation as a protective factor. Emotion regulation is the way individuals manage feelings when faced with tension in their lives. Quantitative research methods are used with non-probability sampling techniques with purposive sampling. The research participants totaled 390 individuals aged 17-27 years. The questionnaire was completed by research participants online and contained three measurement tools, namely the Generalized Anxiety Disorder (GAD-7) measurement tool to measure anxiety, the Family Adaptability and Cohesion Evaluation Scale II (FACES II) and the Family Communication Scale (FCS) to measure family function, and the Emotion regulation Questionnaire (ERQ) to measure emotion regulation. Data processing was done with SPSS ver. 27, and Process Marco Model 1. The results show that emotion regulation in the high reappraisal dimension ( effect = -0.139, p = 0.002) and low suppression dimension ( effect = -0.191, p = 0.000) can be a moderator in the relationship between family functioning and cohesion dimension. Thus, emotion regulation can be a protective factor to minimize individuals experiencing anxiety in the midst of low functioning families.